The story of the Ardalan princes’ library - حسه‌ینی سەید نەجمەدین سه‌باح (The Scientific Journal of Cihan University– Sulaimaniya, 2026)
Author: Dr. Sabah Hosseini Abstract: The history of Kurdistan, especially the history of Kurdish literature, has many obscure and dark points. In this distant history, many events that took place in Kurdistan have not been recorded and we are not aware of them. There have been many who have had thousands of rare books in their libraries, and after their death, these rare libraries have been scattered and a volume of them has been uprooted, and many of them have been destroyed princes, who ruled part of the Kurdish region for more than six hundred years, among whom were a number of literary and poetic people. One of these people is Amanullah II, known as Gholam Shah Khan, who passed away in 1284 AH. After the death of Gholamshah Khan and the end of the rule of the Ardalan dynasty, the library of this dynasty and a significant part of Gholamshah Khan’s property will be auctioned. This article tells the story of this library through notes in several manuscripts